Lincoln's greatcoat : the unlikely odyssey of a presidential relic - Chilton, Reignette G., 1957- (McFarland & Company, Inc., Publishers, 2019)
"Brooks Brothers crafted Abraham Lincoln's greatcoat in honor of his second inauguration. Mrs. Lincoln gave the greatcoat to a White House doorkeeper. The coat was returned to Ford's Theatre, but not before it underwent an exciting journey. This book recounts that journey as a reminder of his call to "bind up wounds" and care for others"--